1996
DOI: 10.1073/pnas.93.20.10928
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian orthologues of a yeast regulator of nonsense transcript stability.

Abstract: All eukaryotes that have been studied to date possess the ability to detect and degrade transcripts that contain a premature signal for the termination of translation. This process of nonsense-mediated RNA decay has been most comprehensively studied

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
87
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(90 citation statements)
references
References 27 publications
2
87
1
Order By: Relevance
“…[34][35][36][37][38] Thus, UPF1 is functionally the most important NMD factor and is the most evolutionarily conserved. 39,40 UPF1 also acts in non-NMD decay pathways, such as staufen1 (STAU1)-mediated mRNA decay (SMD) and replication-dependent histone mRNA decay. 41,42 Gene expression profiles of mammalian cells using siRNA-mediated depletion of UPF1 indicated that a significant fraction of cellular transcripts are upregulated, most of which are considered NMD-sensitive transcripts.…”
Section: Resultsmentioning
confidence: 99%
“…[34][35][36][37][38] Thus, UPF1 is functionally the most important NMD factor and is the most evolutionarily conserved. 39,40 UPF1 also acts in non-NMD decay pathways, such as staufen1 (STAU1)-mediated mRNA decay (SMD) and replication-dependent histone mRNA decay. 41,42 Gene expression profiles of mammalian cells using siRNA-mediated depletion of UPF1 indicated that a significant fraction of cellular transcripts are upregulated, most of which are considered NMD-sensitive transcripts.…”
Section: Resultsmentioning
confidence: 99%
“…The human UPF1 gene encodes a polypeptide with a predicted molecular weight of 130 kDa and shows a strong homology to the cysteine-rich region as well as the helicase superfamily I domain of the yeast UPF1 gene (Perlick et al+, 1996;Applequist et al+, 1997)+ The yeast Upf1p demonstrates a nucleic-acid-dependent ATPase activity and 59 r 39 helicase activity (Czaplinski et al+, 1995)+ These biochemical activities of the Upf1p were utilized to examine the mechanism of Upf1 function in translation termination and mRNA turnover+ The conservation of the helicase domain suggests that HUpf1 protein might have similar biochemical properties to the yeast Upf1p+ Thus, the goal of the experiments described below is to perform a biochemical characterization of the HUpf1 protein+ The HUpf1 protein was purified by constructing a human UPF1 allele harboring a Flag epitope at the amino terminal end of the human UPF1 gene+ This allele was inserted into a Baculovirus transfer vector and the protein was purified from insect cell extracts (High Five)+ A prominent band with the expected size of human Upf1 protein was present specifically in High Five extracts expressing HUpf1 protein, indicating the feasibility of the large scale purification (Fig+ 1A, compare second and third lanes)+ The cell extracts were incubated with anti-FLAG immunoaffinity resin at 4 8C+ The beads, recovered after centrifugation, were washed extensively and the HUpf1 was subsequently eluted by inclusion of the FLAG peptide in the appropriate buffer (see Materials and methods)+ Fractions eluted contained predominantly one band with a molecular weight of ;130 kDa (Fig+ 1B) that reacted with the anti-flag antibody as detected by immunoblotting (Fig+ 1C)+ The purified protein was aliquoted and stored in 10% glycerol-containing buffer at ĎŞ70 8C with no apparent loss of activity over several months+ A nonionic detergent (Triton X-100) was used at 0+01% to stabilize the protein during storage+ We utilized this purified HUpf1 protein to characterize its biochemical properties+…”
Section: Expression and Purification Of Recombinant Human Upf1mentioning
confidence: 99%
“…The yeast UPF1 gene and its protein product have been the most extensively investigated factor in the NMD pathway (Altamura et al+, 1992;Koonin, 1992;Leeds et al+, 1992;Atkin et al+, 1995Atkin et al+, , 1997Czaplinski et al+, 1995Czaplinski et al+, , 1999Cui et al+, 1996;Weng et al+, 1996aWeng et al+, , 1996bWeng et al+, , 1998)+ The Upf1p contains a cysteine-and histidine-rich region near its amino terminus and all the motifs of the superfamily group I helicases+ The yeast Upf1p has been purified and demonstrated to have RNA-binding activity, RNA-dependent ATPase activity, and RNA helicase activity (Czaplinski et al+, 1995, Weng et al+, 1996a, 1996b)+ Disruption of the UPF1 gene results in stabilization of nonsense-containing mRNAs and suppression of certain nonsense alleles (Leeds et al+, 1991;Cui et al+, 1995;Czaplinski et al+, 1995;Weng et al+, 1996aWeng et al+, , 1996b)+ A set of mutations was isolated in the UPF1 gene that separated its mRNA decay function from its activity in modulating translation termination at a nonsense codon (Weng et al+, 1996a(Weng et al+, , 1996b)+ Consistent with the view that the Upf1p is involved in modulating translation termination, recent results have shown that it interacts with the translation termination release factors eRF1 and eRF3 (Czaplinski et al+, 1998(Czaplinski et al+, , 1999)+ These data suggest that the NMD and translation termination pathways are linked (reviewed in Czaplinski et al+, 1998Czaplinski et al+, , 1999)+ Based on these observations, a "surveillance complex" consisting of at least Upf1p, Upf2p, Upf3p, and the release factors has been suggested to modulate translation termination and NMD (Czaplinski et al+, 1998(Czaplinski et al+, , 1999)+ Homologs of the Upf1p have been identified in humans cells (the HUPF1/RENT gene; Perlick et al+, 1996, Applequist et al+, 1997 and in C. elegans (Page et al+, 1999;Jacobson & Peltz, 1996; WORMPEP: Y48G8A 3304+a)+ It is evident that the Upf1p plays a conserved role in NMD...…”
Section: Introductionmentioning
confidence: 99%
“…In most organisms, prokaryotic and eukaryotic, mutations that generate premature translation termination codons in the coding region of genes often result in a significant reduction of the corresponding mRNA+ This phenomenon has been extensively studied in the yeast Saccharomyces cerevisiae and in mammalian systems (Peltz et al+, 1994;Maquat, 1995;Ruizechevarria et al+, 1996)+ In yeast, it seems that premature stop codons trigger an accelerated cytoplasmic mRNA decay that reduces the steady-state level of the transcript+ Rather than being a passive mechanism by which nontranslated mRNA is degraded, it is an active process in which on-going translation plus cis-acting sequences and specific trans-acting factors are required (Leeds et al+, 1991;Cui et al+, 1995;Ruizechevarria et al+, 1996)+ Apart from yeast, the effect of nonsense codons on RNA metabolism has been best studied in mammalian systems (Maquat, 1995)+ Here, however, there is often no difference between the cytoplasmic half-life of mRNAs carrying premature stop codons relative to the corresponding wild-type form+ Instead, it has been observed that these mutations lead to reduced levels of nuclear-associated mRNA+ A reduction of the mRNA that copurifies with nuclei, for example, has been observed in transcripts coding for dihydrofolate reductase (Urlaub et al+, 1989), triose phosphate isomerase (Belgrader et al+, 1994), the mouse major urinary protein (Belgrader & Maquat, 1994), heavy and light chain immunoglobulins, and, more recently, T-cell receptors (Lozano et al+, 1994;Carter et al+, 1996)+ In these cases, the "nuclear" reduction is either through a direct effect on the half-life of the mature nuclear or nuclear-associated mRNA, or through a negative effect on pre-mRNA processing+ For example, studies with transcripts from Ig genes indicate that nonsense codons inhibit splicing (Aoufouchi et al+, 1996)+ However, despite different phenomenologies in yeast and mammalian cells, a mammalian orthologue of Upf1, one of the yeast trans-acting factors required for the nonsense mRNA decay, has been cloned that complements the Upf1-deficiency phenotype in yeast (Perlick et al+, 1996;Applequist et al+, 1997)+…”
Section: Introductionmentioning
confidence: 99%